Determining the significance of coagulase-negative Staphylococci (CoNS) from blood cultures by molecular approach - Rahman, Zaidah Abdul (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Background: Coagulase-negative staphylococci (CoNS) are a group of micro-organisms that are increasingly implicated as a cause of significant infection and the leading cause of blood stream infection (BSI). One important predictor of true BSI is the isolation of CoNS from multiple blood cultures, presuming that the isolates represent the same species. Aim: Thus, the objective of this study was to determine the significance of repeated CoNS isolated from blood cultures. Methods: This was a prospective laboratory study which was initiated in June 2007 until July 2008. CoNS isolates were obtained from patients who had two positive blood cultures within a 14-day interval. CoNS were identified with the species level using an API-Staph and antibiotics susceptibility testing was performed according to the CLSI standard. Strain relatedness was confirmed using pulsed-field gel electrophoresis. Findings: During the study period, 202 of CoNS were isolated from I 01 patients. The most common species isolated was Staphylococcus epidermidis (59.0%). 83.2% of patients isolated same species of Co NS from repeated blood cultures. Among the isolates of same species, only 40. 7% had the same antibiogram. CoNS with the same species and antibiogram had 93.3% probability of the same strain. 65.5% of patients were treated with antibiotics, especially glycopeptides group. Conclusion: Speciation and antibiogram of CoNS from repeated blood cultures are adequate in determining the significance of repeated Co NS isolated from blood cultures.